The impact of built environment on physical activity and subjective well-being of urban residents: A study of core cities in the Yangtze River Delta survey - Zhang, Jing; Zheng, Yan; Wen, Tao; Yang, Min; Feng, Qiang ming (Frontiers in Psychology, 2022)
In cities with high population density in China, the impact of built environment on human health is rather complicated. Physical activities are an important factor in promoting people's health. This study is aimed to explore ways of enhancing the residents’ intensity of physical activities and psychological health in a limited built environment. For this purpose, this study conducted research on 1875 residents from cities in the Yangtze River Delta in China to clarify the complicated correlations among the residents’ physical activities, the multi-dimensional geographic environment characteristics, and subjective well-being. First, Neighborhood Environment Walkability Scale (NEWS-A), International Physical Activity Questionnaire Short Form (IPAQ-SF), and Subjective Well-being Scale for Chinese Citizens (SWBS-CC) were used to measure built environment characteristics, intensity of physical activities, and subjective well-being. Second, the correlations among built environment, physical activities, and subjective well-being were analyzed, which reflected different effects of built environment characteristics on physical activities and subjective well-being. Third, physical activities were viewed as a mediating variable in SEM to analyze the influence mechanism of each built environment characteristic on the subjective well-being of residente. The results show: Residents with different individual characteristics may have different levels of perception and usage of built environment. The intensity of physical activities has significant positive correlations with proximity to supporting facilities, accessibility of destinations, and public security, while no significant correlation with overall environmental aesthetics and street connectivity. The residents’ subjective well-being has significant positive correlations with accessibility of destinations, overall environmental aesthetics, and public security, while no significant correlation with proximity to supporting facilities and street connectivity. Physical activities not only have a direct effect on subjective well-being, but also a mediating effect on the correlations between subjective well-being and built environment characteristics. In the future, more research could be conducted on the optimization of correlations between residential built environment characteristics and physical activities as well as subjective well-being, so as to gain a deeper understanding about the impact of residential built environment on people’s physical and mental health.